Usage of propranolol to attenuate catabolism process in burn victim : A case report - Ishandono Dahlan, Ishandono Dahlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Burn is still a common injury faced by the surgeons. The mortality is considerably high. One of the improvement in the mortality and outcome of the treatment over the last decades can be attributed to the modulation of the hypermetabolic response to trauma. It was reported by researchers in Shrinners Hospital that propranolol administration during the hospitalization attenuates the hypermetabolism and reverses muscle catabolism. Our case is a 16 year old male burn victim admitted to DR Sardjito Hospital, after 24 hour hospitalization in a District Hospital. He was assessed as 40% grade II-III of electric injury. Fluid resuscitation with Baxter Formula and debridement of the wound were performed as the initial treatment. In the first 12 weeks of hospitalization the plasma protein was decreasing due to hypermetabolic response to the severe burn and the albumin concentration was never reach 2 g/L. Thats why the plan to do skin grafting was postponed. It was decided then to apply the Shrinners Hospital protocol, i.e. propranolol administration, to make reversal effect of catabolism. After five weeks of oral propranolol administration the albumin concentration was increasing from 1.8 to 2.9 g/I, so that we could perform split thickness skin grafting procedure. Two weekks later about 95% of the skin graft donor were viable. We came to the conclusion that the administration of oral propranolol could attenuate catabolism process and directly increase the plasma albumin concentration.Keywords : burn - propranolol - hypermetabolism slowing effect - plasma albumin concentration